Pelvic lymph nodes: distribution and nodal tumour burden of urothelial bladder cancer. Issue 6 (3rd April 2010) - Seiler, Roland; von Gunten, Michael; Thalmann, George N; Fleischmann, Achim
Abstract : Aims: To evaluate the number of lymph nodes and the lymph node tumour burden in different anatomical pelvic regions to better asses the impact of variations in the extent of lymphadenectomy on reported LN parameters and pelvic tumour clearance. Methods: 162 patients with lymph-node-positive urothelial carcinoma of the bladder were treated by cystectomy and extended pelvic lymphadenectomy. Various lymph node parameters were determined separately for the three pelvic regions (external iliac, obturator and internal iliac). Results: Of 4080 evaluated lymph nodes (median 25 per patient, range 8–55) 39%, 35% and 26% (p<0.05) were found in the external iliac, obturator and internal iliac region, respectively. The distribution of the 625 lymph node metastases (median two per patient, range 1–35) was not significantly different between the regions (external iliac 33%, obturator 38%, internal iliac 29%). However, the median diameter of largest metastasis and total diameter of all metastases were smallest in the internal iliac region (external iliac 0.85 cm, 1.1 cm; obturator 0.8 cm, 1.0 cm; internal iliac 0.6 cm, 0.8 cm; p<0.03, p<0.05; for median diameter of largest metastasis and total diameter of all metastases, respectively). Metastases in only one region were found in 33% of patients (external iliac 13%, obturator 10%, internal iliac 10%); these three groups showed no significant difference in survival. No difference was detected in lymph node parameters between genders. Conclusions: Lymph node counts and retrieval of metastases depends on the extent of pelvic lymphadenectomy. Dissection not including the internal iliac region misses 26% of all pelvic lymph nodes, 29% of metastases, and understages a substantial number of patients as pN0 (10%).